OPERATING SPECIFICATIONS OF CATALYTIC CLEANING OF GAS FROM BIOMASS GASIFICATION - Lisý, Martin; Baláš, Marek; Špiláček, Michal; Skála, Zdeněk (Acta Polytechnica, 2015)
The paper focuses on the theoretical description of the cleaning of syngas from biomass and waste gasification using catalytic methods, and on the verification of the theory through experiments. The main obstruction to using syngas from fluid gasification of organic matter is the presence of various high-boiling point hydrocarbons (i.e., tar) in the gas. The elimination of tar from the gas is a key factor in subsequent use of the gas in other technologies for cogeneration of electrical energy and heat. The application of a natural or artificial catalyst for catalytic destruction of tar is one of the methods of secondary elimination of tar from syngas. In our experiments, we used a natural catalyst (dolomite or calcium magnesium carbonate) from Horní Lánov with great mechanical and catalytic properties, suitable for our purposes. The advantages of natural catalysts in contrast to artificial catalysts include their availability, low purchase prices and higher resilience to the so-called catalyst poison. Natural calcium catalysts may also capture undesired compounds of sulphure and chlorine. Our paper presents a theoretical description and analysis of catalytic destruction of tar into combustible gas components, and of the impact of dolomite calcination on its efficiency. The efficiency of the technology is verified in laboratories. The facility used for verification was a 150 kW pilot gasification unit with a laboratory catalytic filter. The efficiency of tar elimination reached 99.5%, the tar concentration complied with limits for use of the gas in combustion engines, and the tar content reached approximately 35 mg/mn3. The results of the measurements conducted in laboratories helped us design a pilot technology for catalytic gas cleaning.